(untitled) (Journal of Mechanical Engineering, 2019)
Apparel industry plays an important role in the economic and social development of Bangladesh. This is now a multi-billion dollar manufacturing and export industry in Bangladesh. Its contribution to the foreign exchange earnings, poverty alleviation through creating employment opportunities and empowerment of women is remarkable. However, global competition and unstable market conditions prompted manufacturers to review their traditional manufacturing strategy. In today’s competitive business world, manufacturers are using Lean Manufacturing (LM) technique in order to improve performance and competitiveness. Lean Manufacturing (LM) is a holistic and sustainable approach of manufacturing system used for creating value for customers through eliminating waste in the manufacturing processes. This conceptual paper addresses the concept of lean manufacturing, its benefits and the challenges of implementing lean manufacturing.